Penggunaan Media Sosial Instagram Sebagai Media Promosi Minuman Cocktail Arak Bali - Rusdiarnata, I Ketut (Program Studi Administrasi Perhotelan, 2023)
This study aims to determine the use of Instagram social media as a medium for promoting Balinese arak cocktails and its benefits are expected to contribute to the parties involved, both from academics and practitioners in the field, in this case the Balinese Arak Cocktail entrepreneur. The results of this study indicate that the Arak & Culture business expands its marketing reach and increases sales by utilizing social media Instagram. Promotion through Instagram generates trust for consumers and useful comments for users to find out more information from the images displayed. The marketing strategy carried out by Arak & Culture's efforts in promoting its business through uploading photos and videos on Instagram as well as utilizing existing features on Instagram helps Arak & Culture's efforts to make it easier to promote product variants at no cost. It is recommended that Arak & Culture entrepreneurs from a promotional perspective are expected to be developed so that sales can reach a wider target by using paid Instagram features that have not been tried such as Instagram ads so that the target market is more targeted so that the purpose of the promotion becomes more effective and efficient.